ANALYSIS OF COLLABORATIVE GOVERNANCE STRATEGY OF THREE PILLARS OF STAKEHOLDERS IN ADDRESSING FOOD SECURITY PROBLEMS IN BANDAR SRIBAWONO AREA EASTLAMPUNG - Ismono Hadi; Amantha Goestyari K (Faculty of Social and Political Sciences, Universitas Lampung, 2025)
This study aims to investigate the collaborative governance strategy carried out by head of the Bandar Sribawono district government East Lampung, head of Bandar Agung village government, head of Hamlet 18 and 19, Farmer Group Association (Gapoktan) of Hamlet 18 and 19, Bhayangkara Community Security and Order Supervisor (Bhabinkamtibmas) of Bandar Sribawono Police Sector, and the private sector in overcoming the problem of food security for corn commodities. Collaborative governance as collaboration is a relationship designed to solve problems in this case problems that arise due to food security activities. These problems include: availability of seed, fertilizers, pesticides, land fertility, wage workers, agricultural technology, weather, and agricultural human resources. Through effective collaboration, it is expected to be able to maintain food availability, food access, and food utilities which have become national agendas. The research method used is a qualitative method that focus on descriptive analysis. This qualitative method is to describe how collaboration is carried out to overcome food security problems. Data were collected through interviews with stakeholders. The results of the study show that: collaborative governance is carried out effectively, routinely, and measurably and has succeeded in overcoming the problem food security for corn commodities, such as: 1) availability of sufficient quantities of superior hybrid corn seed NK (Northrup King) Sumo; 2) sufficient subsidized fertilizers such as Urea and NPK Phonska are available; 3) sufficient non-subsidized pesticides such as Emacell, Prevathon and Sapporo are available; 4) land degradation and salination do not occur; 5) land processing still requires a relatively large number of hires labor; 6) modern agricultural technology has not been implemented; 7) weather does not affect corn planting pattern; and 8) agricultural human resources are available in the form of active agricultural extension workers and food security assistance from Bhabinkamtibmas.